Quality of sports physical fitness extracurricular participants - Satrio, Bimo; Winarno, Mashuri Eko (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2019)
This study aims to determine the condition of lung cardiac endurance (VO2 Max) of sports extracurricular participants at SMA Negeri 8 Malang. The research method used was descriptive quantitative with the research subjects of sports extracurricular participants of SMA Negeri 8 Malang numbering to 107 students; 32 students of basketball, 26 students of badminton, 21 students of volleyball, and 28 students of Soccer or futsal. The instrument used was a multistage fitness test with a descriptive quantitative percentage data analysis. The results of the study showed that male members of basketball and futsal had an average VO2 Max between 35.0-38.3 ml/kg/ minute, while badminton and volleyball members had an average VO2 Max less than 35.0 ml/kg/ minute. For the female groups of basketball, volleyball and futsal members, they had an average VO2 Max between 31.0-34.9 ml/kg/ minute, while badminton members had an average VO2 Max between 25.0-30.9 ml/kg/ minute. The conclusions were that male members of basketball and futsal were in the category of "bad" lung endurance, while badminton and volleyball members were in the category of "very bad" lung endurance. Whereas for the female groups, the members of basketball, volleyball, and futsal were in the category of "less" lung endurance, while badminton members were in the category of "bad" lung endurance. To get achievement, physical fitness was very important especially for students who joined extracurricular sports.